Advances in the multifunctionality of cell membrane-encapsulated nanoparticles in the treatment of colorectal cancer - Qiu, Zhengdong; Liu, Wenxuan; Xu, Sheng (Frontiers in Immunology, 2025)
Cell membrane-camouflaged nanoparticles (CNPs) have emerged as promising multifunctional platforms for colorectal cancer therapy, integrating drug delivery, immunomodulation, photothermal ablation, and anti-inflammatory effects. This review highlights recent advances in CNP-based strategies, emphasizing their unique capacity to enhance tumor-targeting specificity, potentiate immunotherapeutic efficacy, and overcome the limitations of conventional treatments. We summarize diverse approaches employing immune cell or tumor cell membrane coatings, as well as hybrid systems that combine CNPs with chemotherapy, metabolic modulation, or photothermal therapy. Accumulating evidence demonstrates that CNPs can effectively remodel the tumor immune microenvironment, increase the bioavailability of hydrophobic drugs, and promote synergistic therapeutic outcomes. Despite these encouraging results, clinical translation remains constrained by challenges in biodegradability, biosafety, large-scale manufacturing, and cost. Ongoing clinical trials are evaluating the safety and therapeutic potential of CNP-based nanomedicines. Overall, this review underscores the transformative role of CNPs as a next-generation platform for precision and personalized therapy in colorectal cancer.